A study of pulmonary function tests in nargile smokers in a single center in tishreen university hospital - حبيب ربى أحمد; الخير محمد; حجوز عقيل (Latakia University Journal -Medical Sciences Series, 2022)
Background: there is an increasing and frightening spread of nargile (waterpipe) smoking globally, which makes studies on its harms, especially long-term ones, disproportionate to the extent of the problem. Despite the definitive relationship between cigarette smoking and the development of COPD, cardiovascular disease and cancer, the relationship of these diseases and nargile smoking and the duration and amount of exposure is not well studied. Aim: The aim of this study is to compare the spirometric profile between exclusive nargile smokers and non-smokers and to study the relationship between these values and the duration of nargile smoking Patients and methods: This is a cross-sectional study. A total of 182 subjects aged 20-60 years were included and divided into two groups: non-smoker group and exclusive nargile smokers A questionnaire was completed for each participant, and spirometry was performed .IBM SSPS statistic was used for data analysis, P-value ≤0.05 was considered as statistically significant. Results: The exclusive nargile smokers (ENS) group and the non-smoker (NS) group were similar in terms of age and gender distribution. The mean FEV1% was significantly lower in ENS group compared to NS group (85.38%± 10 vs. 90.24%± 7.99, p-value=0.0001). A statistically significant decrease in the values of FEV1/FVC, PEF%, MMEF% was also observed. A non-statistically significant difference in the values of FVC and BMI was observed between the two groups. The prevalence of COPD among ENS group was 11%, and these subjects with COPD had a higher smoking rate than those who do not have COPD (49.27±15.2 nargile-year vs. 31.1±14.93 nargile-year). Conclusion: The results of our study suggest that nargile smoking significantly increase the risk of COPD. Given the importance of COPD in the global burden of disease, it is necessary to carry out further studies on the relationship between nargile use and COPD.